A perspective on overcoming water-related stability challenges in molecular and hybrid semiconductors. (March 2020) - Nikolka, Mark
Abstract: Abstract : Molecular semiconductors synergize a variety of uniquely advantageous properties such as excellent absorption and emission properties, soft and deformable mechanical properties, and mixed ionic and electrical conduction. Over the past two decades, this outstanding set of features has put molecular semiconductors in the spotlight for a variety of optoelectronics and sensing applications. When it comes to mass-market adaptation, however, a challenge in these soft and van der Waals-bonded materials remains their electrical as well as environmental stability and degradation. This Prospective will summarize some of our current understanding of why organic semiconductors degrade with a strong emphasis put on the quintessential role played by water in this process. Furthermore, it will be revisited by which mechanisms water-related stability shortcomings might be addressed in the future and how these lessons can be translated to relevant hybrid systems such as perovskites and carbon nanotubes. Throughout this discussion, some parallels and key differences between organic and hybrid materials will be highlighted, and it will be elaborated on how this affects the associated device stability.